More extension work needed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Mr D. Koulangar Ngartoubam, of the ONDR in Chad is musing about a strange rumour which is holding back the growth of soya in his region. 'In this day and age, soya is a very important crop all over the world, as a source of protein and vegetable...